Knee osteoarthritis in professional football is related to severe knee injury and knee surgery - Vincent Gouttebarge; Haruhito Aoki; Gino M. M. J. Kerkhoffs (BMC, 2018)
Abstract Background As a consequence of severe knee injuries, knee osteoarthritis (OA) seems prevalent in retired professional footballers. However, some epidemiological data remain missing, for instance whether knee OA is also prevalent in current professional footballers, whether knee OA is associated with knee injuries and surgeries, and whether knee OA leads to a lower level of functioning. Therefore, three research questions were answered: (i) what is the prevalence of knee osteoarthritis (OA) among current and retired professional footballers? (ii) is severe knee injury or knee surgery associated with knee OA among current and retired professional footballers? (iii) what are the consequences of knee OA on physical knee function among current and retired professional footballers? Methods An observational study based on a cross-sectional design by means of questionnaires was conducted. Participants were current and retired professional footballers recruited by the World Players' Union (FIFPro). Information about severe knee injury and knee OA was gathered (medical record or team doctor), while physical knee function was assessed through a validated scale. Results A total of 1360 participants (964 current and 396 retired professional footballers) were enrolled in the study (response rate of 54%). Prevalence of knee OA was 13% among current players and 28% among retired players (p < 0.01), being higher among older players. Current and retired professional footballers were nearly twice as likely to suffer from knee OA by every additional severe knee injury and by every additional knee surgery (risk ratio: 1.72-1.96; p < 0.01). Current and retired professional footballers with knee OA reported a lower level of physical knee function than current and retired players without OA (p < 0.01), their physical knee function being also lower than reference values (adult population, young athletic population and amateur footballers). Conclusion The prevalence of knee OA was higher among retired than among current professional footballers and reached up to 40%, leading to negative consequences for their physical knee function. Current and retired professional footballers were nearly twice as likely to suffer from knee OA by every additional severe knee injury and by every additional knee surgery incurred during their career. Management of knee OA should be prioritized among professional footballers, especially to prevent the worsening of the condition during their retirement years.